Correction to: Stereotactic radiosurgery and radiotherapy for resected brain metastases: current pattern of care in the Radiosurgery and Stereotactic Radiotherapy Working Group of the German Association for Radiation Oncology (DEGRO) (Strahlentherapie und Onkologie, (2022), 198, 10, (919-925), 10.1007/s00066-022-01991-6) - Rogers, S.; Baumert, B.; Blanck, O.; Boehmer, D.; Bostroem, J.; Engenhart-Cabillic, R.; Ermis, E.; Exner, S.; Guckenberger, M.; Habermehl, D.; Hemmatazad, H.; Henke, G.; et al. (Strahlentherapie und Onkologie, 2023)
In this article the author name S. E. Combs was incorrectly written as S. Combs. The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-08